Answer:
P ( x ) = -0.7 (x - 2)²(x + 3)
Step-by-step explanation:
<u>We are given</u> :
P ( x ) , has a root of multiplicity 2 at x = 2
and a root of multiplicity 1 at x = − 3
Then
P ( x ) = a (x - 2)²(x + 3) ; where ‘a’ is a real number.
P ( x ) = a (x - 2)²(x + 3)
= a (x² - 4x + 4)(x + 3)
= a [x³ - 4x² + 4x + 3x² - 12x + 12]
P (0) = -8.4
⇔ a [(0)³ - 4(0)² + 4(0) + 3(0)² - 12(0) + 12] = -8.4
⇔ 12 a = -8.4
⇔ a = (-8,4) ÷ 12
⇔ a = -0,7
<u>Conclusion</u> :
P ( x ) = -0.7 (x - 2)²(x + 3)
Answer:
3.5 or 3 and a half of a apple
Step-by-step explanation:
You just divide 7 by 2
I am gonna do what you did to me and say its easy.
Answer:
y+4=-36 and the answer is y=-40
Step-by-step explanation:
So the word is means equals, meaning we can change it to say
"y more than 4 = -36
and more than means addition so we can put a plus sign there and we get
y+4=-36
then to solve this equation we need to get y by itself on one side and to do that we can move the 4 to the other side by subtracting it on both sides to cancel out the addition and we get y=-40
I hope this helps and please don't hesitate to ask if there is anything still unclear!
Answer:
5+9+-23
Step-by-step explanation: